A Comparative Study on Optimal Solutions of Flow Shop Scheduling Problems under Fuzzy and Intuitionistic Fuzzy Environment - Uthra, G.; Thangavelu, K.; Shunmugapriya, S. (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
This paper deals with the comparative study on the optimal solutions of flow shop scheduling problem under fuzzy and intuitionistic fuzzy environment. The processing times are represented as generalized intuitionistic triangular and trapezoidal fuzzy numbers which are then defuzzified into crisp values by the efficient centroid ranking method. This paper concludes that problems under intuitionistic environment yields better results and the approach is illustrated with numerical examples.Â Keywords: Fuzzy flow shop scheduling problem, Generalized Intuitionistic Trapezoidal Fuzzy Number, Branch and Bound, job block criteria.